Finance and Development, March 2014. (Finance and Development; Finance and Development ;, 2014)
This chapter discusses the story of European integration in what is known as the European Union. The decision in 1951 by six European nations to pool coal and steel production under a common authority-the European Coal and Steel Community-marked the beginning of European integration. French statesman and political visionary Robert Schuman proposed the coal and steel community in 1950. The chapter also highlights that the 28-member European Union, built around common policies and shared institutions, has proved robust to many challenges and has accommodated great change used by 18 countries. The European Union was also awarded the 2012 Nobel Peace Prize. The study shows that the 2008 global financial crisis laid bare fault lines, exposing tensions between EU members and stresses and gaps in institutions and policies that Europe's political leaders are working hard to address. The IMF's chief for Europe argues that what Europe needs is more integration, not less.